ANALYSIS OF POVERTY IN FOREST SURROUNDING COMMUNITIES BY SUSTAINABLE LIVELIHOOD APPROACH - Rita Parmawati; Soemarno Soemarno; Maryunani Maryunani; Agung Sih Kurnianto (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2018)
Poverty in forests surrounding communities shows a contrast between wealth of forest resources and poverty. The poverty of forests surrounding communities is seen as inefficient development to rural needs in general and forest management in particular. This study aims to analyze the factors affecting poverty, the relevance and Sustainable Livelihood Approach in poverty. This research was conducted in Argosari Village, Jabung Subdistrict and Mentaraman Village, Donomulyo District, Malang Regency. Sustainable livelihood approach is applied which adapted on five elements: human, natural, physical, social and financial asset. The sample was determined by proportional random sampling method. Participatory Rapid Appraisal (PRA) were used in this study. Quantitative approach in this study using descriptive analysis and Structural Equation Modeling (SEM). Poverti Gap 2 indicator (the number of family member) has the greatest contribution to Argosari poverty. The High Consumption 3 indicator (the number of new clothing in a year that can be bought) has the smallest contribution. Significantly, eight indicators have established in Mentaraman, which is indicated by a p-value less than 5% (0.05). Based on the size of the standardize coefficient, it is found that the Poverti Gap 2 indicator (the number of family member) has the greatest contribution to Mentaraman  poverty. Keywords : Argosari, Forest, Mentaraman, Poverty, SLA